2020
DOI: 10.3389/fnana.2020.00003
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Genoarchitecture of the Basal Hypothalamus in Zebrafish Embryos

Abstract: Analyses of genoarchitecture recently stimulated substantial revisions of anatomical models for the developing hypothalamus in mammalian and other vertebrate systems. The prosomeric model proposes the hypothalamus to be derived from the secondary prosencephalon, and to consist of alar and basal regions. The basal hypothalamus can further be subdivided into tuberal and mamillary regions, each with distinct subregions. Albeit being a widely used model system for neurodevelopmental studies, no detailed genoarchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 68 publications
(111 reference statements)
4
58
1
Order By: Relevance
“…The prosomeric model is uniquely consistent with the multitude of brain developmental gene expression patterns accrued during the last 40 years, which were meaningless within the columnar model. It can explain many neurogenetic, axonal navigational and patterning data, and applies in other vertebrates (Puelles, 1995 ; Croizier et al, 2014 ; Domínguez et al, 2014 , 2015 ; Santos-Durán et al, 2015 , 2016 , 2018 ; Nieuwenhuys and Puelles, 2016 ; Gonzalez et al, 2017 ; Schredelseker and Driever, 2020 ). Several recent monographs present structural and functional vertebrate neuroanatomy, including that of the human brain, based on the prosomeric model (Watson et al, 2010 ; Striedter, 2016 ; ten Donkelaar, 2018 , 2020 ; Schröder et al, 2020 ; Striedter and Northcutt, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The prosomeric model is uniquely consistent with the multitude of brain developmental gene expression patterns accrued during the last 40 years, which were meaningless within the columnar model. It can explain many neurogenetic, axonal navigational and patterning data, and applies in other vertebrates (Puelles, 1995 ; Croizier et al, 2014 ; Domínguez et al, 2014 , 2015 ; Santos-Durán et al, 2015 , 2016 , 2018 ; Nieuwenhuys and Puelles, 2016 ; Gonzalez et al, 2017 ; Schredelseker and Driever, 2020 ). Several recent monographs present structural and functional vertebrate neuroanatomy, including that of the human brain, based on the prosomeric model (Watson et al, 2010 ; Striedter, 2016 ; ten Donkelaar, 2018 , 2020 ; Schröder et al, 2020 ; Striedter and Northcutt, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
“…The prosomeric model reveals a shared genoarchitectonic hypothalamic structure in amniotes and anamniotes (Shimogori et al, 2010 ; Diez-Roux et al, 2011 ; Moreno et al, 2012 ; Puelles et al, 2012 , 2013 ; Puelles, 2013 ; Domínguez et al, 2014 ; Morales-Delgado et al, 2014 ; Díaz et al, 2015 ; Ferran et al, 2015 ; Puelles and Rubenstein, 2015 ; Santos-Durán et al, 2015 , 2016 , 2018 ; Schredelseker and Driever, 2020 ). Affaticati et al ( 2015 ) and Yamamoto et al ( 2017 ) largely confirmed this shared molecular pattern in zebrafish but suggested an alternative vision of the preoptic domain.…”
Section: The Hypothalamus In the Updated Prosomeric Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…1. See list of abbreviations for complete terms Puelles and Rubenstein 2003;Lauter et al 2013;Dominguez et al 2014Dominguez et al , 2015Nieuwenhuys and Puelles 2016;Puelles 2018;Schredelseker and Driever 2020). We applied the principles of the prosomeric model to a topological analysis of architectonic landmarks to trace adult hypothalamic nuclei to their likely developmental origin in rhesus monkeys, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%